Mapping ozone risks for rice in China for years 2000 and 2020 with flux-based and exposure-based doses - Tang, Haoye; Pang, Jing; Zhang, Gongxuan; Takigawa, Masayuki; Liu, Gang; Zhu, Jianguo; Kobayashi, Kazuhiko (Atmospheric environment (1994), 2014)
We parameterized a multiplicative model of stomatal conductance (gsto) for O3 uptake by rice leaves with the field measurements in a fully open-air ozone (O3) fumigation experiment. The estimated gsto compared well with the observed one (r2 = 0.79). By using the gsto model for O3 uptake, we estimated a flux-based O3 risk (POD6, accumulated stomatal flux of O3 above a threshold of 6 nmol m−2 s−1) for rice across China in years 2000 and 2020, and compared it with the exposure-based O3 risk (AOT40, accumulated hourly O3 concentration above 40 ppb during daytime) for the same period. For the year 2000, both POD6 and AOT40 indicated the middle and lower reaches of Yangtze River and the south China being at the highest O3 risk. From the years 2000–2020, the O3 risks are projected to double (POD6) or triple (AOT40) in a majority of rice producing areas in the above two regions. Among three major rice cropping in the middle and lower reaches of Yangtze River, double-late rice is projected to have lower O3 risk than double-early rice and single rice on the either O3 risk measure in both 2000 and 2020. In south China, on the other hand, the O3 risks for double-late rice are comparable to that for early double-rice. In this study, the O3 risk was not measured as yield loss but as O3 flux and O3 exposure. The crop loss estimation would require a relationship between O3 flux and yield loss for major rice production regions across China. •Ozone flux to rice leaves was modeled with observations in free-air fumigation.•Surface ozone concentration in China was estimated with a chemical transport model.•Ozone risks on the flux and exposures were estimated for China in 2000 and 2020.•Rice regions along the Yangtze River and south China had high ozone risks in 2000.•The ozone risks will double or triple from 2000 to 2020 in the major rice regions.